Association of the acute:chronic workload ratio and wellness scores in premier league male hockey players - Torres, G.; Veiga, G.; Maposa, I. (South African Journal of Sports Medicine, 2021)
Background: The relationship between acute:chronic workload ratios (ACWR) and the incidence of injury, as well as the relationship between subjective wellness scores and training load, is unclear in hockey players.